The Influence Socio-Demographic and Psychological Factors Toward Energy Use Behavior to Adoption Energy-Efficiency Products (Journal of Innovation, Business and Entrepreneurship, 2020)
Indonesia is one of the big countries that consume energy and is under tremendous pressure to promote saving energy and reduce domestic energy consumption. A variety of intervention approaches have been studied to encourage energy-saving actions in order to minimize energy usage by performing energy saving. The research focused on the relative importance of socio-demographic variables and psychological variables in energy use and energy saving behavior. This research proposes a method that incorporates social-psychology to analyze determinants of energy saving behavior with an integrated MOA (motivation - opportunity - capacity) system. The proposed structure is expected to provide insight into strategy intervention and adoption of energy efficiency products that are in line with Indonesia's behavior energy use for successful energy saving measures to reduce overall energy consumption.Keywords: Energy consumption, Electricity saving behavior, Energy use characteristic, MOA model, Multiple Linear Regression